LOVE’S REPRESENTATION IN KALAM EINEH LYRICS:A SEMIOTIC PERSPECTIVE BY ROLAND BARTHES: REPRESENTASI CINTA DALAM LIRIK LAGU KALAM EINEH: SEBUAH PERSPEKTIF SEMIOTIKA OLEH ROLAND BARTHES - Muhamad Saiful Mukminin (Muaddib: Journal of Arabic Language and Literature, 2024)
The research aims to explore the denotative, connotative, and mythological meanings of the lyrics of Kalam Eineh by Sherine Abdel Wahab. It employs a qualitative descriptive approach with textual analysis. The data are obtained from the song lyrics sourced from YouTube. The analysis is conducted in three stages according to Roland Barthes' semiotic model. First, denotative meaning is analyzed through literal interpretation. Second, connotative meaning is examined to identify emotional values and symbols. Third, mythological meaning is analyzed to uncover broader cultural narratives. The findings indicate that the lyrics of Kalam Eineh reflect a complex experience of love. At the denotative level, love is depicted through the symbolism of the eyes and intimate gestures, while at the connotative level, the lyrics emphasize sacrifice and emotional harmony. In terms of myth, love is understood as a magical force that transcends human limitations, creating a reflection of Arab cultural values in the context of interpersonal relationships